PENDIDIKAN BERBASIS NILAI –NILAI PROFETIK DI MIN PURWOKERTO - Dwi Priyanto; Rifqi Abdul Rosyad (IAIN Purwokerto, 2017)
Abstract: The result of research indicates that: 1) Management of education based on prophetic values in MIN Purwokerto Banyumas Regency is implemented as follows: a) The new student recruitment system of MIN Purwokerto is conducted by non-test selection, by interview, the number of new students accepted is limited the amount is in accordance with the capacity of the provided classes are 4 classes or 128 students, because one class maximum of 32 students. b) MIN Purwokerto has Panca Prasetya learners, namely: 1) familiarize and implement the rules and regulations of madrasah, 2) respect the parents and teachers, 3) commitment to maintain the facilities and infrastructure Madrasah, 4) fostering in itself to behave with akhlakul karimah, 5) cooperate and be faithful to friends. Panca prasetya learners is a loyal oath of MIN Purwokerto students to be practiced in everyday life both in the environment of madrasah and in society Prophetic values implanted in students MIN Purwokerto namely: honest, discipline, responsibility, hard work, simple, independent, fair, brave and caring; Keywords: Education, values, prophetic and Islamic elementary school